The influence of acclimatization, age and gender-related differences on thermal perception in university buildings: Case studies in Scotland and England. (15th July 2020) - Jowkar, Mina; Rijal, Hom Bahadur; Montazami, Azadeh; Brusey, James; Temeljotov-Salaj, Alenka
Abstract: The higher education sector in the UK is responsible for large amount of the country's energy consumption. Space heating, which is the largest and most expensive part of the energy used in the UK educational buildings is a potential target for improving energy efficiency. However, the role of thermal comfort in students' productivity in academic environments cannot be overlooked. Considering the prevalence of two different climatic conditions in Northern and Southern/Midland regions of the UK, this study investigated thermal comfort in two university campuses in Scotland and England. environmental measurements combined with a simultaneous questionnaire survey were conducted in eight university buildings in Edinburgh and Coventry. The field study was carried out during the academic year of 2017-18 on 3507 students. The results confirmed influence of students' acclimatization, showing a warmer than neutral mean Thermal Sensation Vote (TSV) and cooler thermal preference in Edinburgh than Coventry. The higher acceptable temperature in Coventry (23.5 °C) than Edinburgh (22.1 °C) reinforced the results on the influence of climatic adaptation. Thermal acceptability was examined in a direct (analysing the actual votes on thermal acceptability) and an indirect approach (considering the TSV between −1 and 1 as acceptable). The indirect approach was shown to be a better predictor of the thermal acceptability as this method extends beyond the acceptable range suggested by the direct method. Thermal perceptions of females were shown to be colder than males in university classrooms. However, no statistically significant difference was observed in the thermal comfort of different age groups. Highlights: Thermal comfort perception differs for university students in England and Scotland. Comfort temperature is higher in England than Scotland as a result of acclimatization. Warmer thermal sensation and cooler preference are observed in England than Scotland. Women have cooler sensations and warmer preferences than men in university classrooms. Similar thermal comfort perception is observed for all age groups.